2020
DOI: 10.1051/0004-6361/202037469
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray properties of radio-selected blazars

Abstract: Context. Hard X-ray properties of beamed AGN have been published in the 105-month Swift/BAT catalog, but there have not been any studies carried out so far on a well-defined, radio-selected sample of low-peaked blazars in the hard X-ray band. Aims. Using the statistically complete MOJAVE-1 sample, we aim to determine the hard X-ray properties of radio-selected blazars, including the enigmatic group of gamma-ray-faint blazars. Additionally, we aim to determine the contribution of radio-selected lowpeaked blazar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…4 the X-ray space density obtained from the integration of the XLF considering the effect of CMB (solid red line). The shaded areas show the expected evolutions assuming a different photon index (Γ in the range 1.5-1.6, the median values observed at energies 20-100 keV in a radio selected sample of blazars, Langejahn et al 2020) and a different distribution of the logA 0 parameter which can still well reproduce the observed C19 X/R ratios (p-value>0.7, see section 3). As it is clear from Fig.…”
Section: Comparing X-ray and Radio Resultsmentioning
confidence: 91%
“…4 the X-ray space density obtained from the integration of the XLF considering the effect of CMB (solid red line). The shaded areas show the expected evolutions assuming a different photon index (Γ in the range 1.5-1.6, the median values observed at energies 20-100 keV in a radio selected sample of blazars, Langejahn et al 2020) and a different distribution of the logA 0 parameter which can still well reproduce the observed C19 X/R ratios (p-value>0.7, see section 3). As it is clear from Fig.…”
Section: Comparing X-ray and Radio Resultsmentioning
confidence: 91%
“…However, Pal et al (2020) reported a strong soft X-ray excess in the X-ray spectrum of OJ287 using XMM-Newton observations. Furthermore, Langejahn et al (2020) showed that the Swift-BAT spectrum (20-100 keV) is well-described by a power-law with Γ = 1.31, using the 105months Swift-BAT survey. NuSTAR observed OJ287 twice during two major flare events detected by Swift (in 2017 and 2020): although the 3.0-10.0 keV X-ray flux was similar ( 3.5 × 10 −12 erg cm −2 s −1 ) during these observations, the photon index varied.…”
Section: Oj 287mentioning
confidence: 96%